New Quinoxalines with Biological Applications - Vieira, Mónica (2019)
In search of alternatives to antimicrobial agents currently in use, and in order to respond to the landscape of loss of efficacy due to the emergence of resistance, several research groups are evaluating several familiesof compounds, among them the quinoxaline derivatives family, which presented several other potential biological applications.